Effect of Clerodendrum serratum leaf extract on biochemical and oxidative stress parameters of testis in 7, 12-dimethylbenz[a]anthracene induced skin carcinogenesis in Swiss albino mice - Chinchali, Jayaraj F; Sanakal, Rajeshwari D; Kaliwal, Basappa B (Recent Research in Science and Technology, 2012)
The biochemical contents and antioxidant potential of Clerodendrum serratum (Verbenaceae) leaf extract (CSLE) on 7, 12-dimethylbenz[a]anthracene (DMBA) induced skin carcinogenicity in testis of mice was investigated. Group I received distilled water served as control. The skin lesions were induced by twice-weekly topical application of DMBA for 2 weeks on the shaved backs of group II, III, IV and V mice. CSLE was administered to group III, IV and V mice at the dose of 300, 600 and 900 mg/kg b.wt/day, for 4 week before DMBA application, and continued till 45 days. On 46th day the mice were sacrificed, testis were dissected out freed from adherent tissue and weighed to nearest milligram and evaluated the biochemical contents DNA, RNA, protein, glycogen, cholesterol, lactate dehydrogenase (LDH), Succinic dehydrogenase (SDH), acid phosphatase (ACP) and alkaline phosphatase (AKP) activities, oxidative stress parameters, levels of glutathione (GSH), thiobarbaturic acid reactive substances (TBARS), superoxide dismutase (SOD), catalase (CAT) and glutathione-s-transferase (GST). DMBA induced skin carcinogenesis decreased body and testis weight, DNA, RNA, protein, glycogen, GSH level, SDH, AKP, SOD, CAT and GST activities. But there was increase in cholesterol content, LDH, ACP activities and TBARS level. DMBA act via generating reactive oxygen species (ROS) as tumor initiator and free radicals inducing oxidative stress. The results revealed that there was a recovery in biochemical contents, dehydrogenases, phosphatases and oxidative stress parameters in testis. Thus, the present study inferred that CSLE administration significantly curtailed tumor development and counteracted all the biochemical effects. Many plant secondary metabolites exhibit potent anticarcinogenic potential and known to exert their effects by quenching reactive oxygen, inhibiting lipid peroxidation.